The Effectiveness of The Role of the National Narcotics Agency in the City of Gorontalo in Preventing Drug Distribution - Isa, Mohamad Rizky; Puluhulawa, Irlan (Universitas Negeri Gorontalo, 2024)
This study aims to identify and analyze the role of the Gorontalo City National Narcotics Agency (BNN) in preventing drug trafficking from the perspective of legal effectiveness and the challenges it faces. Using normative-empirical research with statutory and case approaches, the study finds that the legal framework and law enforcement factors are adequate but require increased capacity and resources. Facilities are sufficient but need laboratory upgrades. Community involvement must be strengthened, and deviant cultural behaviors among officials need elimination. Overall, the BNN's role is effective, but enhancements in these areas are necessary. Challenges include low community participation, poor public understanding of narcotics regulations, and insufficient funding for eradication efforts.